Cordotomy in mesothelioma-related pain: a systematic review. Issue 1 (18th September 2013) - France, Barbara D; Lewis, Ruth A; Sharma, Manohar L; Poolman, Marlise
Abstract : Background: Cordotomy can be effective in relieving pain for patients with mesothelioma, but the evidence to support continued provision is limited. This review forms part of the Invasive Neurodestructive Procedures in Cancer Pain pilot study: The role of cordotomy in mesothelioma-related pain in the UK. Aim/design: We report on the results of the first comprehensive systematic review of the use of cordotomy in mesothelioma-related pain, with specific reference to effectiveness in relieving pain and safety. The review was conducted according to guidelines reported in the NHS Centre for Reviews and Dissemination and the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines for systematic reviews and meta-analyses. Data sources: 14 databases from inception to March 2012 were searched, with no limitations on language or publication type. Results: Nine studies met the inclusion criteria, all of which were case series of percutaneous cervical cordotomy (PCC) involving 160 patients. All studies demonstrated good pain relief in the majority of patients. Initial post-procedure measurements showed the greatest reduction in pain. Some side effects (headache, mirror pain, motor weakness) occurred relatively frequently but were mostly transient. Respiratory dysfunction post-PCC was rare. No deaths were directly ascribed to cordotomy. Conclusions: The available evidence is significantly limited in quantity and quality. Although it seems to suggest that cordotomy might be safe and effective in this setting, more reliable evidence is needed to aid decision making on continued provision. A national registry for cordotomy would be a valuable first step in this process.